The Role of Motivation and Leadership Style in Improving the Quality of Employee Performance in Covid-19 Pandemic Period: A Case study of Private Universities in Jakarta - Nidaul Izzah; Samsudin; Supriyono (Technium Social Sciences Journal, 2020)
The Covid-19 pandemic has made major changes in human life as a whole, including changes in the world of work and the way of working. Everyone has different experiences when it comes to adapting. However, adaptation is not something easy, because it occurs in a very short time, and is immediately practiced in real life. One of the consequences of the Covid-19 outbreak is a change in the work system from work from office (WFO) to work from home (WFH). With this system change, the employees’ condition will also change, in this case, a decrease in work motivation. This study is aimed at answering the questions of what barriers employees face in carrying out work from home (WFH) and how universities improve the quality of their employees’ performance so that they can work optimally during the Covid-19 pandemic. This study applies a phenomenological approach from qualitative research design. In this study a semi-structured interview is employed. The research proved that motivation and leadership style are two factors that have an important role to improve employee work performance. This study contributes significantly to the development of human resources management. In addition, the results of this study can be used as input for authorized institutions in the improvement of human resources performance in private universities.